Calculation of Foundation Structure and Design Planning of The Building of The Faculty of Civil Engineering and Planning, Gunung Jati University, Cirebon - Wikal Tyas Adhiwiyatno; Trio Galih Hartaro; Yoga Pamungkas; Sumarman Sumarman (Riviera Publishing, 2025)
The